Romanen som vitalistisk form - Frank, Søren (K&K - Kultur og Klasse, 2006)
Salman Rushdies The Ground Beneath Her Feet The novel as a vitalistic form This article discusses the relationship between life (understood as becoming) and form in novelistic practice in general by taking as its starting point the ideas of novelistic form and the position of the narrator in Lukács, Benjamin, Adorno and Deleuze. More specifically, the article examines the relationship between life and form in Salman Rushdie’s The Ground Beneath Her Feet and argues that the novel can be regarded as an example of ‘vitalistic form’. The concept of vitalistic form entails that the novel’s form not merely reflects Rushdie’s understanding of life as process and becoming; in addition, the form itself is metamorphic and transgressive in its discursive strategies (e.g. narratorial self-correction, metafictional traits, ontological complementarity and uncertainty in regard to the status of the fictional universe(s)).